Research on students' emotion and behavior in online learning / Nur Farhana Suliman - Suliman, Nur Farhana (2012)
Education lifestyle is moving and changing with the technologies from the traditional learning to online learning. There are many research conducted in this area. However, there is still lack of research that study both the students' emotion and behavior in online learning and it affects towards students' engagement in the online learning course. The objectives of this research is to identify student's emotion in online learning course, to capture student's behavior in online learning course that in this research focus on online database course specimen and to identify the relationship between student's emotion and behavior in online learning and it affects to student's engagement in online database course. To achieve this several experiment and survey conducted in order to validate both the emotional and behavior condition of the students. Kansei Engineering technique is used in this research to achieve the emotions words. The emotions words from the Kansei Engineering technique is than reduced to 30 words by making a comparisons with the Russell's 'Circumplex Model of Affect' and together with the Kort's 'Four Quadrant Model'. A web analysis tool using Clicky Analytics is used in this research to achieve the second objectives. The findings from the log records and the emotion survey are than further used to accomplish the third objectives. The results of the experiment and survey conducted shows that there are a relationship between emotion and behavior towards students' engagement in database course. The findings can help designers to gain extra knowledge in designing or developing the online course and to assist educators to make wise decisions in designing the online course to tailor with the teaching methods and processes.